Synthesis and Applications of Onium Salts for Photopolymerization Reactions - Abu-Abdoun, Ideisan I.; Aale-Ali, Aale-Ali (Journal of Research Updates in Polymer Science, 2024)
The synthesis and characterization of phosphonium and arsonium salts having anthraquinone and anthracene moiety was carried out by reacting equimolar amounts of halomethyl anthracene or anthraquinone with triphenylphosphine or triphenyl arsine in toluene solvent. The halide counter (Cl or Br) ion was exchanged with hexafluoro antimonate (SbF6-) which proved to be a useful photoinitiator for polymerizing cyclohexene oxide, styrene, p-methyl styrene, and N-vinylcarbazole. The experimental results demonstrate the effects of salt, monomer structures, and the photolysis time on the rate of polymerization and the number average molecular weight of the obtained polymer. These salts are easy to handle, nonhygroscopic under laboratory conditions, and they have good solubility in halogenated solvents such as dichloromethane and chloroform.